Resiliensi Mualaaf Laki-Laki Pasca Kekerasan Dalam Beragama - Ikrima Sabrina; Rina Mariana (Psyche 165 Journal, 2019)
purpose of this study was to determine the description of resilience in male converts after religious violence. The subjects in this study were one person and male. The research method used in this study is a qualitative research method with a case study research design. Based on the research that the researcher examined that the subject had good resilience. In this study, the results of the study concluded that aspects of resilience such as emotional regulation include: 1) regulating emotions in certain situations and conditions. In this section the subject regulates emotions well. 2) evaluating emotions and understanding the cause, in this section the subject has a fairly good emotional evaluation, 3) controlling the situation in this part of the sub-ec can control the situation quite well. Impulse Control, includes: 1) things that push themselves towards decisions taken by the subject can push themselves towards decisions that are taken well. Optimism, includes: 1) trusting oneself, the subject has a good sense of optimism. 2) Confidence in things that are focused on things that are focused on subjects having things that focus well. Causal analysis, includes: 1) the ability to believe in people, in this case the subject has a good ability to believe in people. 2) the strength possessed of the desire, the subject has a very good desire, Empathy, includes: 1) understanding how the situation and self-condition with people In this case the subject has good empathy Self Efficacy, including: 1) how to overcome the problem, the subject can overcome the problem well. Reaching Out, includes: 1) things that make it rise, the subject can rise well. Towards things that make the subject stronger on his decision 2) achievements that have been carried out, the wishes of all subjects are achieved well.